Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3389/fnhum.2014.00249
|View full text |Cite
|
Sign up to set email alerts
|

A cross-linguistic evaluation of script-specific effects on fMRI lateralization in late second language readers

Abstract: Behavioral and neuroimaging studies have provided evidence that reading is strongly left lateralized, and the degree of this pattern of functional lateralization can be indicative of reading competence. However, it remains unclear whether functional lateralization differs between the first (L1) and second (L2) languages in bilingual L2 readers. This question is particularly important when the particular script, or orthography, learned by the L2 readers is markedly different from their L1 script. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Still several authors found, at the group level, that Chinese/Japanese character recognition induces slightly more right-lateralized VOTC activations than alphabetical reading (e.g. Bolger et al, 2005; Feng et al, 2020; Koyama et al, 2014; Qu et al, 2019; Szwed et al, 2014; Tan et al, 2001). We did not find such rightward bias, possibly because our participants were native Chinese speakers, while the rightward bias may be specific to logographic scripts acquired as a second language (for a review see Cao, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Still several authors found, at the group level, that Chinese/Japanese character recognition induces slightly more right-lateralized VOTC activations than alphabetical reading (e.g. Bolger et al, 2005; Feng et al, 2020; Koyama et al, 2014; Qu et al, 2019; Szwed et al, 2014; Tan et al, 2001). We did not find such rightward bias, possibly because our participants were native Chinese speakers, while the rightward bias may be specific to logographic scripts acquired as a second language (for a review see Cao, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggest inter-hemispheric cooperation is less likely to emerge during pre-lexical (perceptual) and/or post-lexical (decisionmaking) processing, but mainly occurred during lexical semantic processing when the semantic information was shared between hemispheres. Koyama et al (2014) tested whether left-lateralized fMRI activations for reading differ between first (L1) and second (L2) languages in bilingual L2 readers. They asked late L2 learners to perform a visual one-back matching task either in English or Japanese.…”
mentioning
confidence: 99%
“…Their findings suggest inter-hemispheric cooperation is less likely to emerge during pre-lexical (perceptual) and/or post-lexical (decision-making) processing, but mainly occurred during lexical semantic processing when the semantic information was shared between hemispheres. Koyama et al ( 2014 ) tested whether left-lateralized fMRI activations for reading differ between first (L1) and second (L2) languages in bilingual L2 readers. They asked late L2 learners to perform a visual one-back matching task either in English or Japanese.…”
mentioning
confidence: 99%